Connection between type 2 diabetes and depression and their common influence on quality of life - Lačković, Milena (Medicinski podmladak, 2024)
Type 2 diabetes mellitus (DM2) and depression are chronic non-communicable diseases that affect millions of people worldwide. The comorbidity of these two diseases is a complex phenomenon and has a huge clinical significance. The association between DM2 and depression was recognized decades ago, however the cause of the high prevalence of this comorbidity is not fully understood. It is assumed that shared genetic and environmental risk factors play a role, such as certain gene polymorphisms related to the secretion and effects of cortisol, obesity and others. Pathophysiological mechanisms underlying depression, such as HPA axis dysregulation and inflammation, impair insulin resistance and contribute to the development of DM2, while on the other hand, chronic stress linked to DM2 may cause depression. This relationship, which is often described as bidirectional, leads to the formation of the so-called "vicious cycle" that results in poor health outcomes of both conditions. Patients with DM2 and comorbid depression have a higher incidence of long-term complications, primarily macrovascular, lower quality of life and a higher mortality rate. Therefore, the prevention, early detection and treatment of depression in DM2 is extremely important. The treatment of comorbidity of these diseases include a multidisciplinary approach aimed at the simultaneous improvement of mental and physical health. Treatment involves pharmacotherapy, psychotherapy and psychosocial interventions, with the main goal of reducing the incidence of DM2 complications and improving the quality of life of affected individuals.
Keywords: Keywords: diabetes mellitus type 2, depression, comorbidity, risk factors, quality of life